O Colono na cidade: memórias e viveres rural-urbanos em Marechal Cândido Rondon (Oeste do Paraná, 1970-2009) - Pagliarini, Raphael (2009)
This research discuss about the Marechal Cândido Rondon urbanization process through the dialogue with the memories and the life of former-farmers who had lived deeply this process, mainly from the 1970s. Although it is currently travestied among de powerful spheres as an essentially urban aura, in the city this agricultural life and practice survive and it is re-elaborated. It is discussed, thus, the uses and the permanence sense of agricultural life values and knowledge. This work is concerned to the symbolic disputes consisting and constituent in the daily practice, in which it is delineated territories and it is acted in its own way, different, many times, to the agenda proposed of industrialization recent elaborated in the scope of economic and politics interests from the elites. At the same time, the city is opened to the reinsertion expectations for many workers, the urban life is produced in a net of tensions, lacks and claims. The city is narrated, thus, as a space and an object of dispute, in relations that are established between the most diverse scopes: in the classroom, between genders, ethnic, and also the peasants identities related to the urban world. Methodologically, it fits in the Oral History field, from which it is discussed how the citizens remember their process of experience in the city in different temporalities